Developing Islamic-values-based PowToon learning media for Muhammadiyah kindergarten teachers: COVID-19 and TEYL - Rifky Dora Wijayati; Khafidhoh (English Language Teaching Educational Journal, 2022)
In response to the COVID-19 epidemic, this study intends to establish a digital learning media for children based on Islamic values utilizing PowToon for Muhammadiyah kindergarten teachers. Online learning has replaced traditional classroom for teaching and learning. During the COVID-19 pandemic, an online discussion with TK ABA Nitikan teachers established the significance of this research. They were concerned about propounding digital learning materials with Islamic values to students. The Islamic fundamentals, such as greetings and du'a (prayer), are crucial for the development of Islamic character in young learners. In addition, the digital learning resources were transformed into videos that could be easily accessible, shared, and used publicly to promote the da'wah practice in accordance with Muhammadiyah's guidance. This research employed a Research and Development (R&D) approach utilizing the ADDIE model known as system approach developed by Dick and Carey (2015), which entails a development process comprising five primary stages, namely analyze, design, develop, implement, and evaluate. The research findings indicate that the digital learning materials created using PowToon met the needs of TK ABA Nitikan teachers were relevant. The manufactured product provides a solution to teachers' needs by merging both general English knowledge and Islamic beliefs. Based on the review, it has been determined that the created content is of excellent quality. This material allowed teachers to teach English in an engaging manner.